Junior Senior Farewell - Unknown:::Creator::::::::::::
Photograph shows the Junior Senior Farewell held on June 23, 1914 in the Quad at San Jose State Normal School. Photograph shows students lined up on either side of a walkway, some are holding arches of flowers, walking deown the isle and through the arches. The students marching down the aisle are wearing solid white headbands with writing on them. The students lining the walk way are wearing whiite headbands that are split.